Is Learning Motivation Can Affect Students’ Problem-Solving Skills in Junior High School? A Correlation Study - Quini, Ira Fadriani; Latifah, Annisa Gina; Aripin, Usman ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2025)
Problem solving refers to the process of finding ways to overcome challenges in order to achieve specific goals. In mathematics learning, problem-solving skills must be instilled from an early stage so that students are trained to solve both mathematical problems and real-life challenges. According to Polya, the steps in problem solving include understanding the problem, devising a solution strategy, implementing the strategy, and evaluating the results. Learning motivation is an internal and external drive that encourages students to enjoy and engage enthusiastically in the learning process. This motivation helps students attain optimal academic performance, as strong motivation during learning is likely to produce better outcomes. In other words, individuals with strong motivation tend to achieve better academic results. The purpose of this study is to analyze the correlation between students' learning motivation and their mathematical problem-solving skills at the junior high school level. The participants in this study were 24 students from class VIII.I at SMP Krida Utama Padalarang. The research method used was correlational analysis. Data were collected using a learning motivation questionnaire consisting of 10 positive and 10 negative statements, along with a mathematical problem-solving test on flat-sided solid shapes comprising four essay questions. The results of the study indicate a significant and strong correlation between learning motivation and mathematical problem-solving skills among junior high school students. Regression analysis shows a positive relationship in which higher learning motivation leads to greater problem-solving skills. These research findings provide insights for teachers and researchers to recognize the importance of learning motivation as a key factor in enhancing students' problem-solving skills.